Characterization of coarse particulate matter in school gyms - Braniš, Martin; Šafránek, Jiří (Environmental research, 2011)
We investigated the mass concentration, mineral composition and morphology of particles resuspended by children during scheduled physical education in urban, suburban and rural elementary school gyms in Prague (Czech Republic). Cascade impactors were deployed to sample the particulate matter. Two fractions of coarse particulate matter (PM(10-2.5) and PM(2.5-1.0)) were characterized by gravimetry, energy dispersive X-ray spectrometry and scanning electron microscopy. Two indicators of human activity, the number of exercising children and the number of physical education hours, were also recorded. Lower mass concentrations of coarse particulate matter were recorded outdoors (average PM(10-2.5) 4.1-7.4 μg m(-3) and PM(2.5-1.0) 2.0-3.3 μg m(-3)) than indoors (average PM(10-2.5) 13.6-26.7 μg m(-3) and PM(2.5-1.0) 3.7-7.4 μg m(-3)). The indoor concentrations of coarse aerosol were elevated during days with scheduled physical education with an average indoor-outdoor (I/O) ratio of 2.5-16.3 for the PM(10-2.5) and 1.4-4.8 for the PM(2.5-1.0) values. Under extreme conditions, the I/O ratios reached 180 (PM(10-2.5)) and 19.1 (PM(2.5-1.0)). The multiple regression analysis based on the number of students and outdoor coarse PM as independent variables showed that the main predictor of the indoor coarse PM concentrations is the number of students in the gym. The effect of outdoor coarse PM was weak and inconsistent. The regression models for the three schools explained 60-70% of the particular dataset variability. X-ray spectrometry revealed 6 main groups of minerals contributing to resuspended indoor dust. The most abundant particles were those of crustal origin composed of Si, Al, O and Ca. Scanning electron microscopy showed that, in addition to numerous inorganic particles, various types of fibers and particularly skin scales make up the main part of the resuspended dust in the gyms. In conclusion, school gyms were found to be indoor microenvironments with high concentrations of coarse particulate matter, which can contribute to increased short-term inhalation exposure of exercising children.
Keywords: pevné částice; Air Pollution, Indoor; velikost částic; dítě; monitorování životního prostředí; Particle Size; lidé; Particulate Matter; školy; inhalační expozice; Schools; gymnastika; znečištění vzduchu ve vnitřním prostředí; Air Pollutants; Czech Republic; Environmental Monitoring; Česká republika; Child; látky znečišťující vzduch; Gymnastics; Inhalation Exposure; Humans